Story telling with our students techniques for telling tales from around the world - Heathfield, David (Delta teacher development series, 2014)
Introduces you to the art of telling an unscripted story, and provides you with the opportunity to bring stories from many cultures to vibrant life in your language teaching. This book includes stories from around the world - and focuses on the telling techniques that will make all the difference as you tell them.